The Newly Discovered Topological Theory of Quantum Gravity(TTQG) ‐ A Multiblock Compatibilizer Cum Modifier of the Existing Theories of Physics, Cosmology, Quantum Mechanics and Quantum Computing (Global Journal of Science Frontier Research, 2023)
Abstract not found